La seguridad del paciente en la atención de enfermería en el servicio de Gineco obstetricia del Hospital General Martín Icaza de la ciudad de Babahoyo periodo abril-septiembre 2019 - Martínez Pilco, María José (2019)
The present research work called, the safety of the patient in nursing care in the gynecology obstetrics service at the Martín Icaza General Hospital in the city of Babahoyo period April-September 2019, aims to determine the compliance of the patient's safety in nursing care in the gynecology obstetrics service. It is a descriptive level study, with a quantitative, descriptive, bibliographic, prospective, transverse and field design. The study was carried out with the nursing staff, being a total of 30 people, to which an evaluation instrument was applied, resulting in the Gynecology Obstetrics service with excellent results (3.33%), good (30 %), regular (60%) and bad (6.67%). In addition, with the observation in 2 moments, it was possible to verify the application of safe practices in patient care 52.62% comply and 47.38% do not comply. When socializing the results obtained in the service, 45% of the professionals who were evaluated and observed, attached to these were assisted by medical staff and nursing students.